4-H Swine Record Book 2 - Debbie Glauer (EDIS)
Swine Record Book II (4H SWR 11) is an animal sciences publication suggested for 4-H members ages 13 and up. This book can be used after the Swine Record Book I (4H SWR 10). This record book includes a form to take into account the amount of money borrowed to raise your pig. The companion to this record book is Swine Project Manual Book II (4H SWM 11).